1992
DOI: 10.1073/pnas.89.14.6550
|View full text |Cite
|
Sign up to set email alerts
|

A 39-kDa protein on activated helper T cells binds CD40 and transduces the signal for cognate activation of B cells.

Abstract: CD40 is a B-cell surface molecule that has been shown to induce B-cell growth upon ligation with monoclonal antibodies. This report shows that triggering via CD40 is essential for the activation of resting B cells by helper T cells (Th)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
420
1
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 743 publications
(434 citation statements)
references
References 29 publications
10
420
1
3
Order By: Relevance
“…Recently Shoker et al (32) demonstrated heightened CD154 gene expression in CD4+ T-lymphocytes during acute and chronic renal rejection, which correlated with the severity of rejection. In contrast to other reported results they demonstrated constitutive CD154 gene expression in PBMCs (12,(33)(34)(35)(36)(37).…”
Section: Discussioncontrasting
confidence: 99%
“…Recently Shoker et al (32) demonstrated heightened CD154 gene expression in CD4+ T-lymphocytes during acute and chronic renal rejection, which correlated with the severity of rejection. In contrast to other reported results they demonstrated constitutive CD154 gene expression in PBMCs (12,(33)(34)(35)(36)(37).…”
Section: Discussioncontrasting
confidence: 99%
“…The Ad5/F35-IL2 used in this study may allow these problems to be overcome. Similarly, CD40 ligand (CD40L, also known as gp39 and CD154) is essential in T/B cell interaction 49,50 and for maturation of APC. 16,47 For example, the lack of CD40L on T cell leads to X-linked hyper-IgM syndrome, 51 and in many leukemias, T cell anergy has been attributed to defective CD40L expression by the malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first cognate interactions between B cells and CD4 + T cells occur at the interface between the T‐ and B‐cell zones in lymphoid tissues 95. T‐cell‐mediated ligation of CD40 on the B cell triggers B‐cell clonal expansion and differentiation,96 and cytokines produced by the T cell including interleukin (IL)‐21 and IL‐4 promote growth and differentiation and direct Ig class switching 97, 98. Provision of help is dependent on an active two‐way interaction between the B and T cell, with inducible T‐cell costimulatory (ICOS) triggering being important for IL‐21 production99 and IL‐4 production being dependent on signaling lymphocytic activation molecule (SLAM) 100.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%